Strategies for successfully meeting the demands of quality and service excellence - Verster, Basie (Acta Structilia, 1998)
The management of quality is crucial to business survival and merits the personal attention and commitment of executive management, but the primary responsibility for quality lies with those who perform the work. To enable production teams to accept responsibility for quality output, management must establish systems for control and verification of that output and must educate and train the workforce in the execution of duty. This training in techniques to achieve quality standards, will be repaid many times over by greater output, less waste, an improved product and higher profits.